Do We Need Heparin Coating for Extracorporeal Membrane Oxygenation? New Concepts and Controversial Positions About Coating Surfaces of Extracorporeal Circuits. Issue 2 (8th July 2014) - Silvetti, Simona; Koster, Andreas; Pappalardo, Federico
Abstract Blood contact with surfaces of the extracorporeal circuit provokes the activation of the coagulation system. To improve biocompatibility of the extracorporeal circuit without increasing the risk of bleeding, coatings of artificial surfaces were designed; many of them involve the use of heparin. Data in the literature show that heparin‐induced thrombocytopenia is a major issue in the extracorporeal membrane oxygenation scenario, and no relevant benefits have been shown comparing heparin and no‐heparin coating.